Do model polymer therapeutics sufficiently diffuse through articular cartilage to be a viable therapeutic route?. (26th November 2017) - Powell, Alison; Caterson, Bruce; Hughes, Clare; Paul, Alison; James, Craig; Hopkins, Stephen; Mansour, Omar; Griffiths, Peter
Abstract: The ability of a polymer therapeutic to access the appropriate subcellular location is crucial to its efficacy and is defined to a large part by the many and complex cellular biological and biochemical barriers such that a construct must traverse. It is shown here that model dextrin conjugates are able to pass through a cartilaginous extracellular matrix into chondrocytes, with little perturbation of the matrix structure, indicating that targeting of potential therapeutics through a cartilaginous extracellular matrix should be proven possible. Rapid chondrocytic targeting of drugs which require intra cellularisation for their activity and uniform extracellular concentrations of drugs with an extracellular target, is thus enabled though polymer conjugation.